EFISIENSI PERDAGANGAN ENERGI INDONESIA DENGAN NEGARA DI ASIA TIMUR - Desti Candrasari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The objective of this research is to find out Indonesia’s energy trade efficiency to East Asia countries (Japan, South Korea and China). Indonesia’s energy efficiency trade analyzed by gravity method and Malmquist Index approach. Gravity model used to identify the determinants for the input of trade efficiency, meanwhile Malmquist Index approach used to identify the efficiency. This research will take period 2000-2015. The findings shows the determinants of the energy trade that used as input is population of importer countries, Indonesia population, relative distance and ratio of industry value-added over GDP. Indonesia energy trade efficiency to East Asia countries composed by technical change or trade potential. In average, China has the highest efficiency and show improvement. South Korea also shows an improvement, meanwhile Japan show deterioration.Keywords: Trade Efficiency, Energy, Malmquist Index.